Sport-specific injury mechanisms and situational patterns of ACL injuries: a comprehensive systematic review - Sundberg, A.; Högberg, J.; Tosarelli, F.; Buckthorpe, M.; Della Villa, F.; Hägglund, M.; Samuelsson, K.; Hamrin Senorski, E. (Sports Medicine, 2025)
Background: Anterior cruciate ligament (ACL) injury mechanisms are linked to distinct characteristics and situational patterns inherent to each sport. Understanding ACL mechanisms and situational patterns is crucial to tailor prevention strategies and end-stage rehabilitation practices, ultimately aiming to reduce the incidence of ACL injuries in sports. Objectives: We aimed to compile and synthesize data regarding the injury mechanism and sport-specific situational patterns leading to ACL injuries across various sports. Methods: We conducted a systematic search using MEDLINE, Embase, Cochrane Library, Allied and Complementary Medicine Database, and Physiotherapy Evidence Database in December 2022 and repeated in October 2023 to identify additional published articles. English-language articles investigating ACL injury mechanism, injury situations, and sport-specific situational patterns were included, without restrictions on publication dates. Data extraction was performed independently by two authors. Article quality assessment was conducted with the Quality Appraisal for Sports Injury Video Analysis Studies checklist for video analysis studies and with the JBI Critical Appraisal Checklist for Case Series for athlete- and medical staff-reported studies. The data on ACL injury mechanism, situational patterns, and biomechanics were synthesized into qualitative tables by sport. Biomechanical data of ankle, knee, and hip angles in the sagittal plane for football and basketball were quantitatively synthesized and illustrated using box plots. Results: This systematic review included 62 articles covering 20 sports and 5612 ACL injury situations. The distribution of non-contact, indirect contact, and direct contact ACL injuries varied by sport, reflecting each sport`s unique playing patterns and characteristics. Four main ACL injury categories were identified: (1) change of direction; (2) landing after a jump; (3) direct contact to the knee; and (4) gear-induced mechanisms. In team sports, change of direction injuries ranged from 26 to 70%. Landing injuries were most prevalent in sports involving overhead play, such as volleyball and badminton, accounting for 57-82% of ACL injuries. Direct contact to the knee was the leading cause of ACL injuries in combat sports (53-83%) but also significant in aggressive contact sports such as American Football and rugby. Gear-induced ACL injuries in alpine skiing and board sports occur because of the extended lever arm attached to the feet, and present specific injury mechanisms such as `valgus-external rotation,` `slip and catch,` and `tail landing.` Conclusions: The nature of ACL injuries varies significantly between sports, influenced by injury mechanism and sport-specific situational patterns. We propose a categorization system for ACL injury situations—change of direction, landing, direct contact, and gear-induced situation—based on the findings of this systematic review. This framework aims to facilitate the development of prevention and rehabilitation strategies transferable across various sports and their sport-specific patterns.